Duchenne Muscular Dystrophy: Dari Kesadaran Genetik Menuju Kualitas Hidup yang Lebih Baik - Ar Rochmah, Mawaddah (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
Duchenne Muscular Dystrophy (DMD) is one of the most common genetic neuromuscular disorders in boys, despite being a rare disease. Inherited in an X-linked recessive pattern, DMD carries severe consequences not only for the patient but also for their family. A mother who is a carrier is likely to pass the DMD gene mutation to her son, with a real risk of having a generation with progressive muscle weakness from an early age. Awareness of this inheritance pattern is crucial, given that early diagnosis through genetic screening can provide crucial information for families to take appropriate medical and psychosocial measures. DMD is more than just a muscle disease. Its impact is far-reaching on the quality of life of children, who over time can lose the ability to walk, experience cardiopulmonary complications, and become dependent on intensive care. Families face significant physical, emotional, and financial burdens. Therefore, medical intervention and psychosocial support are crucial. The quality of life of patients and their families must be the primary focus of treatment, not only to prolong life but also to ensure a more meaningful childhood and adolescence. In many developed countries, the development of gene therapy has opened a new chapter in the treatment of DMD. This approach targets the underlying cause of the disease—mutations in the dystrophin gene—thus enabling molecular improvements in muscle function. While still facing challenges in terms of cost, access, and long-term evaluation, this therapy has significantly improved survival rates and slowed disease progression. Meanwhile, in Indonesia, DMD treatment is still dominated by conservative therapy. Corticosteroids, physiotherapy, nutritional support, occupational therapy, and cardiopulmonary management are the main pillars. This multidisciplinary care has been proven to slow progression, improve quality of life, and extend life expectancy, which can now reach the third decade of life with good management. While different from gene therapy practices abroad, conservative therapy still offers significant benefits when implemented consistently and comprehensively. Public awareness of genetic diseases like DMD needs to be increased. The label "rare disease" often keeps it out of the public eye, despite the fact that cases are real and not infrequent. Education about the importance of genetic screening, understanding inheritance patterns, and social acceptance of children with DMD will strengthen the support families need. Furthermore, the involvement of policymakers in expanding access to genetic diagnostics and paving the way for innovative therapies in the future will significantly determine the direction of DMD management in Indonesia. DMD teaches us that genetic diseases are not just clinical issues, but also social and humanitarian ones. Children with DMD deserve a better quality of life, with solid medical, family, and community support. The momentum of increasing public awareness about genetic diseases must continue to be encouraged to reduce stigma, increase access to services, and give every child born with DMD the opportunity for a more meaningful life.